From Hamiltonian Dreams to Maastricht Reality: “Whatever It Takes” 2.0? - Bernatavičius, Marijus (Politologija, 2023)
During the COVID-19 pandemic, the institutional architecture of the euro area has been tested again. While some authors argue that European policy makers have learnt from their economic policy mistakes during the sovereign debt crisis, or even talk about the “European Hamiltonian moment”, the opportunity to fundamentally strengthen the institutional foundations of the currency union has been missed again. While public attention has been focused mostly on the creation of the so-called “Next Generation EU” (NGEU) fund, it was the ECB that quietly performed the key role of crisis manager, despite criticism of a weak initial crisis response and botched communication. Based on the synthetic framework of the classical integration theories, the principal-agent model and new intergovernmentalism, the ECB’s pandemic crisis response could be interpreted as its second “whatever it takes” moment.